The association of traumatic brain injury with rate of progression of cognitive and functional impairment in a population-based cohort of Alzheimer's disease: the Cache County Dementia Progression Study*. (October 2014) - Gilbert, Mac; Snyder, Christine; Corcoran, Chris; Norton, Maria C.; Lyketsos, Constantine G.; Tschanz, JoAnn T.
ABSTRACT Background: There is limited research on factors that influence the rate of progression in Alzheimer's disease (AD). A history of traumatic brain injury (TBI) is associated with an increased risk for AD, but its role on the rate of dementia progression after the onset of AD has not been examined. Methods: A population-based cohort of 325 persons with incident AD was followed for up to 11 years. The sample was 65% female with a mean (SD) age of dementia onset = 84.4 (6.4) years. History of TBI was categorized as number, severity (with or without loss of consciousness), and timing in relation to dementia onset (within ten years or more than ten years). Cognition was assessed by the Consortium to Establish a Registry of AD battery, and functional ability was assessed by the Clinical Dementia Rating Sum of Boxes. Results: In linear mixed models, a history of TBI within ten years of onset showed faster progression of functional impairment (LR x2 = 10.27, p = 0.006), while those with TBI more than ten years before dementia onset had higher scores on a measure of list learning (β = 1.61, p = 0.003) and semantic memory (β = 0.75, p = 0.0035). Conclusions: History of TBI and its recency may be a useful factor to predict functional progression in the course of AD.